Projeto de motor monocilindro de pesquisas termodinâmicas - Santos, Igor Rodrigues dos (2023)
The approval of vehicles with gasoline direct injection (GDI) engines, which new emission and efficiency requirements, is a challenge. Ultra-high pressure direct injection (UHPDI) in spark-ignition engines brings significant thermodynamic advantages and is one of the possible solutions to overcome this challenge. Due to the need to research the advantages of using this technology, the design, dimensioning, and construction of a prototype of a single-cylinder research engine (SCRE) were carried out. The SCRE was developed based on the Integrated Product Development Process, which consists of four main phases: (1) informational design, (2) concept design, (3) preliminary design, and (4) detailed design. During the informational design phase, the identified requirements for the SCRE were converted into design specifications. In the concept design phase, the engine framework concept was defined, where the overall function was broken down into elementary functions within the functional framework, resulting in the definition of three main modules: (1) power unit, (2) cylinder block, (3) base block. From these, a configuration of 500 components was specified, of which only 19% are manufactured, accelerating the development and construction process. The main components were sized, including: (1) cylinder block, (2) crankshaft, and (3) synchronization system. The cylinder block was sized for a peak pressure of up to 200 bar. The crankshaft was sized for infinite fatigue life under the M53 standard with a minimum acceptability factor of 1.15, with operational limits of 22.5 bar indicated mean effective pressure (IMEP) at 800 rpm and 30 bar IMEP at 4500 rpm. However, due to design parameter limitations, the maximum cylinder pressure load for infinite fatigue life achieved was 150 bar. The synchronization system was designed considering a valve command drive power of 0.37 kW, which, due to geometric issues, required the sizing of a reduction box. A cost estimate showed that the prototype construction required an amount of R$ 79,581.00, and its development cost was R$ 234,400.00, totalling R$ 314,251.00. All engine components were manufactured and reworked for assembly, installation, and instrumentation in a test cell. A verification test was at 10 bar IMEP @ 2000 rpm, assessing the influence of injection pressure on engine performance, demonstrating that the designed SCRE meets the need for obtaining data for the research. As of the preparation of this document, the engine has operated for over 36 hours.